Kevin and Peter: responses to two 'preventable deaths'. Issue 5 (3rd September 2018) - Simpson, Graeme; Nowacki, Katja
ABSTRACT: European welfare states have substantial provision to ensure that children are brought up in conditions that meet the articles of the United Nations' Convention of the Rights of the Child. In our analysis of two preventable deaths in Germany and England, we focus primarily on Article 18, which directs states to ensure that there is adequate provision to support parents in their responsibilities, and Article 19, which ensures children's safety and protection. We outline the legal framework, which existed at the time of two child deaths: Kevin from Bremen and Peter in London, both young children who were subject to formal state supervision and oversight. The events – including the press response, their aftermath and the subsequent changes to social work practice through legislation and guidance will be examined. Our subsequent analysis will evaluate the extent to which events altered the balance between Articles 18 and 19 in the two countries, and the extent to which a Children's Rights approach in this area offers new insights. The analysis will suggest that a rights-based approach offers some benefits for a comparative framework and understanding child and family social work, but also that it is not without some difficulties.